2005
DOI: 10.1080/02699050500149858
|View full text |Cite
|
Sign up to set email alerts
|

Assessing recovery in middle cerebral artery stroke using functional MRI

Abstract: With recovery, greater recruitment was observed of the affected primary motor cortex (M1) and a decrease in activation of the unaffected M1 and supplementary motor area. In addition, the widespread activation of brain areas seen during the initial session changed to a more focused pattern of activation as the patient recovered. Imagery tasks resulted in similar brain activity as overt execution pointing to imagery as a potential tool for rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(87 reference statements)
0
10
0
1
Order By: Relevance
“…Therefore, if not properly addressed, these inter-subject variations in brain structures for normal individuals, children, older adults as well as the patient groups can result in imperfect compensations for brain region discrepancies after the spatial transformation (Argall et al, 2006;Hoeksma et al, 2005;Nair et al, 2005;Rademacher et al, 1993;Wilke et al, 2002). Moreover, the morphological differences between individuals in tested subjects and the brain template may lead to localization errors of the activation foci and/or result in decreased fMRI sensitivity in multi-subject studies Toga and Thompson, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, if not properly addressed, these inter-subject variations in brain structures for normal individuals, children, older adults as well as the patient groups can result in imperfect compensations for brain region discrepancies after the spatial transformation (Argall et al, 2006;Hoeksma et al, 2005;Nair et al, 2005;Rademacher et al, 1993;Wilke et al, 2002). Moreover, the morphological differences between individuals in tested subjects and the brain template may lead to localization errors of the activation foci and/or result in decreased fMRI sensitivity in multi-subject studies Toga and Thompson, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…15 The superior parietal lobule (BA 7) and the parietal precuneus are also involved in remembering and executing the correct order of task components and visuomotor function. 16,17 Moreover, the left superior temporal and bilateral inferior frontal gyri play a role in ideation of voluntary simple movement. 18 The right-left asymmetry in our findings might simply be an epiphenomenon reflecting differences in vascular embolic distribution between the right and left circulations in our relatively small cohort.…”
Section: Predicting Left Leg Motor Deficit Improvementmentioning
confidence: 99%
“…Lotze et al were the first to demonstrate activation of the SMC with MI [39], and a large number of subsequent fMRI studies have confirmed this initial finding [22, 40]. MI of fingers, tongue, and toes activated a particular area of SMC, and only MI of fingers activated the SMC area representing fingers.…”
Section: Discussionmentioning
confidence: 97%